MEASUREMENT OF RETINAL DISPLACEMENT AND METAMORPHOPSIA AFTER EPIRETINAL MEMBRANE OR MACULAR HOLE SURGERY. Issue 4 (April 2016) - Rodrigues, Ian A.; Lee, Edward J.; Williamson, Tom H.
Abstract : Purpose: To quantify retinal displacement and metamorphopsia after surgery for epiretinal membrane (ERM) or full-thickness macular hole (FTMH). Methods: Fundus autofluorescence imaging was analyzed for evidence of retinal displacement. Displacement was quantified using a novel standardized approach with measures of vertical interarcade distance, fovea to disk margin, and perimacular area. The vertical disk diameter and normal fellow eyes served as controls. Metamorphopsia was quantified using the Morphision test. Results: Thirty-three eyes of 33 consecutive patients underwent vitrectomy (21 for ERM; 12 for FTMH). After surgery for ERM, the macula expanded (perimacular area: +10.14%, P < 0.0001; intraarcade distance: +6.10%, P < 0.0001; fovea to disk margin: +4.80%, P = 0.0042). Conversely, after surgery for FTMH the macula parameters showed evidence of constriction (interarcade distance: −2.11%, P = 0.0047; perimacular area: −2.95%, P = 0.0197; fovea to disk margin: −4.69%, P = 0.0010). The degree of change in intraarcade distance and perimacular area was greater for the ERM compared with the FTMH ( P < 0.0001). The vertical disk diameter was not altered by surgery for either the ERM or the FTMH. The average change in any measurements between visits in control eyes was just 0.61%, representing high test–retest reliability. Preoperative morphision distortion scores were worse with FTMH (57.3%) than ERM (38%, P = 0.0636) and improved overall after surgery (43.6–21.3%, P = 0.0019). Conclusion: Serial fundus autofluorescence imaging, with the measurement parameters used here, is a reliable means of monitoring retinal blood vessel movement over time. Significant retinal displacement occurs after vitrectomy for FTMH and ERM with the retina expanding after ERM removal and contracting after FTMH closure, with associated improvements in measured metamorphopsia. Abstract : Macular topography can significantly change after epiretinal membrane or macular hole surgery, with the perimacular area affected most significantly. These changes can readily and reliably be quantified using fundus autofluorescence images with routinely available software.